The textile bog find from Vong in Denmark - Mannering, Ulla; Rimstad, Charlotte; Skals, Irene (Archaeological Textiles Review, 2021)
In 1950, Margrethe Hald published an unremarkable textile find from a peat bog called Vong in Denmark. The find has now been 14C dated to the 15th century CE, placing it in a time period for which few textiles are preserved. Although the precise clothing type cannot yet be recognised, the Vong bog find sheds new light on textile types and their uses and reuse in the Late Medieval period.